The PB2 and M genes are critical for the superiority of genotype S H9N2 virus to genotype H in optimizing viral fitness of H5Nx and H7N9 avian influenza viruses in mice. Issue 2 (8th November 2019) - Hao, Xiaoli; Hu, Jiao; Wang, Xiaoquan; Gu, Min; Wang, Jiongjiong; Liu, Dong; Gao, Zhao; Chen, Yu; Gao, Ruyi; Li, Xiuli; Hu, Zenglei; Hu, Shunlin; et al.
Abstract: Genotype S H9N2 avian influenza virus, which has been predominant in China since 2010, contributed its entire internal gene cassette to the genesis of novel reassortant influenza viruses, including H5Nx, H7N9 and H10N8 viruses that pose great threat to poultry and humans. A key feature of the genotype S H9N2 virus is the substitution of G1‐like M and PB2 genes for the earlier F/98‐like M and PB2 of genotype H virus. However, how this gene substitution has influenced viral adaptability of emerging influenza viruses in mammals remains unclear. We report here that reassortant H5Nx and H7N9 viruses with the genotype S internal gene cassette displayed enhanced replication and virulence over those with genotype H internal gene cassette in cell cultures as well as in the mouse models. We showed that the G1‐like PB2 gene was associated with increased polymerase activity and improved nuclear accumulation compared with the F/98‐like counterpart, while the G1‐like M gene facilitated effective translocation of RNP to cytoplasm. Our findings suggest that the genotype S H9N2 internal gene cassette, which possesses G1‐like M and PB2 genes, is superior to that of genotype H, in optimizing viral fitness, and thus have implications for assessing the potential risk of these gene introductions to generate emerging influenza viruses.